Childhood cancer research in oxford III: The work of CCRG on ionising radiation. Issue 6 (11th September 2018) - Kendall, Gerald; Bithell, John; Bunch, Kathryn; Draper, Gerald; Kroll, Mary; Murphy, Michael; Stiller, Charles; Vincent, Tim
Abstract Background High doses of ionising radiation are a known cause of childhood cancer and great public and professional interest attaches to possible links between childhood cancer and lower doses, particularly of man-made radiation. This paper describes work done by the Childhood Cancer Research Group (CCRG) on this topic Methods Most UK investigations have made use of the National Registry of Childhood Tumours and associated controls. Epidemiological investigations have included national incidence and mortality analyses, geographical investigations, record linkage and case-control studies. Dosimetric studies use biokinetic and dosimetric modelling. Results This paper reviews the work of the CCRG on the association between exposure to ionising radiation and childhood cancer, 1975–2014. Conclusion The work of CCRG has been influential in developing understanding of the causes of 'clusters' of childhood cancer and the risks arising from exposure to ionising radiation both natural and man-made. Some clusters around nuclear installations have certainly been observed, but ionising radiation does not seem to be a plausible cause. The group's work has also been instrumental in discounting the hypothesis that paternal preconception irradiation was a cause of childhood cancers and has demonstrated an increased leukaemia risk for children exposed to higher levels of natural gamma-ray radiation.